2015
DOI: 10.1108/jmp-08-2013-0262
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial cognitions in academia: exploring gender differences

Abstract: Purpose – The purpose of this paper is to draw from an adapted model of the Theory of Planned Behaviour and from existing models of entrepreneurial intention (EI) to analyse the role of gender on academics’ perceptions concerning the commercialisation of their research results. In particular, the authors explore differences in perceptions arising from diverse cognitions, such as attitudes towards entrepreneurial activities, the influence of close social groups and opportunity recognition self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 65 publications
4
20
1
Order By: Relevance
“…The insignificant relationship between norms and investment intentions should not be considered evidence inconsistent with the core assumptions of the TPB (Ajzen and Fishbein, 2005). This could be explained by our findings regarding the mediating role of attitudes and control on the relationship between norms and investment intentions, which is in line with previous research in the entrepreneurial domain (Alonso-Galicia et al, 2015, Entrialgo and Iglesias, 2016, Liñán, 2008, Liñán and Chen, 2009, Liñán et al, 2011, Liñán et al, 2013). This full mediation suggests that supportive social circles regarding Greeks' decisions to engage in investment activities create positive attitudes regarding the outcomes that can be gained through the involvement in investment activities, and increase the level of confidence in engaging in investment activities, which in turn lead to the formation of higher investment intentions.…”
Section: Investment Intentions Across Cultural Backgroundssupporting
confidence: 92%
See 1 more Smart Citation
“…The insignificant relationship between norms and investment intentions should not be considered evidence inconsistent with the core assumptions of the TPB (Ajzen and Fishbein, 2005). This could be explained by our findings regarding the mediating role of attitudes and control on the relationship between norms and investment intentions, which is in line with previous research in the entrepreneurial domain (Alonso-Galicia et al, 2015, Entrialgo and Iglesias, 2016, Liñán, 2008, Liñán and Chen, 2009, Liñán et al, 2011, Liñán et al, 2013). This full mediation suggests that supportive social circles regarding Greeks' decisions to engage in investment activities create positive attitudes regarding the outcomes that can be gained through the involvement in investment activities, and increase the level of confidence in engaging in investment activities, which in turn lead to the formation of higher investment intentions.…”
Section: Investment Intentions Across Cultural Backgroundssupporting
confidence: 92%
“…In the Greek group, individuals' investment intentions are formed based on their positive attitudes regarding their engagement in investment activities, which is in line with previous research not only in Greece (for employed/unemployed individuals see Palamida et al, in press; for University students see Zampetakis et al, 2016) but also in other collectivistic societies (India, Iran and Senegal) among university students (García-Rodríguez et al, 2015, Karimi et al, in press, Roy et al, in press) and academics (Spain;Alonso-Galicia et al, 2015). The vast majority of previous studies have reported a significant relationship (e.g.…”
Section: Investment Intentions Across Cultural Backgroundssupporting
confidence: 84%
“…The structural model of the research shows a 57.6% explanation of the variance of AEI. This percentage is higher than those obtained by previous studies academic entrepreneurship between 35 and 50% (Alonso-Galicia et al, 2015;Feola et al, 2017;Fernández-Pérez et al, 2014).…”
Section: Discussioncontrasting
confidence: 74%
“…The study conducted by Pablo-Lerchundi et al (2015) showed that the profession carried out by parents influences the entrepreneurial intentions of students, who were more likely to choose an entrepreneurial career if their parents were entrepreneurs than children of public officials. In recent years, the impact of role models on entrepreneurial process was confirmed in different professional categories, as in academic entrepreneurs (Fernández-Pérez et al, 2015) and active entrepreneurs (Bosma et al, 2012;Fritsch et al, 2012).…”
Section: Cluster 3: Parental Role Models and Entrepreneurial Intentiomentioning
confidence: 96%